Birds in The Air Tawar Campus of Padang State University, West Sumatra. - Fingki Alvia Candra; Ramadhan Sumarmin (Universitas Negeri Padang, 2020)
Abstract. Birds bodiversity affected by habitat conditions and the human activity, as well as bird diversity in Padang State University campus. Padang State University campus is currently experiencing physical changes due to the construction and renovations carried out in seven faculties which have resulted in the loss of green areas which are actually habitat for birds. Previously there was no research on the birds on the UNP campus before there were renovations and construction on the UNP campus. This research was conducted from January to March 2019. Observations were made using the Visual Ecounter Survey (VES) method and combined with the count point method (Point count). Observations are made in the morning (6:00 - 09:00 WIB) and in the afternoon (16:00 - 18:00 WIB). The results of this study indicate that there were 21 species of birds from 15 families. The birds that dominate at the UNP campus area are the genus Passer and Lonchura. While birds that are rarely observed are genera Nectarinia, Copsychus and Eudynamys. The location of the UNP campus adjacent to the beach is also one of the factors that influence the diversity of bird species in this area, as evidenced by the presence of the Ardea sumatrana Cangak laut water bird species. kata kunci: UNP campus, birds, conservation, inventory.